2018
DOI: 10.1097/qai.0000000000001572
|View full text |Cite
|
Sign up to set email alerts
|

Country of Birth of Children With Diagnosed HIV Infection in the United States, 2008–2014

Abstract: The increasing number of foreign-born children with diagnosed HIV infection in the United States requires specific considerations for care and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Overall, 25 of the articles focus on infectious diseases [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The literature indicates high rates of human immunodeficiency virus (HIV) infection in AMC [ 45 , 46 , 47 , 48 , 49 , 50 ], and Germany [ 51 ]. Studies in Israel and Belgium found a high prevalence of mother-to-child HIV transmissions [ 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 25 of the articles focus on infectious diseases [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The literature indicates high rates of human immunodeficiency virus (HIV) infection in AMC [ 45 , 46 , 47 , 48 , 49 , 50 ], and Germany [ 51 ]. Studies in Israel and Belgium found a high prevalence of mother-to-child HIV transmissions [ 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Israel and Belgium found a high prevalence of mother-to-child HIV transmissions [ 45 , 48 ]. AMC living with HIV in the United States and the Netherlands are often diagnosed in the host country, with antiretroviral therapy started at an older age [ 47 , 50 ] However, HIV-infected parents migrating to Sweden are unlikely to disclose their status to their children due to fear of double stigma [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, 91 youths younger than 13 years were diagnosed with HIV in the U.S., and 66 of them had confirmed perinatally acquired infection [2]. In addition, internationally born youth with perinatally acquired HIV (IB-YPHIV) represent a steadily growing majority of pediatric and adolescent HIV cases in the U.S., now accounting for 70% of YLWH younger than 13 years [3]. Developmentally appropriate disclosure of HIV status to YLWH, among many other medical and psychosocial issues that providers need to address, increases the likelihood of optimal health outcomes for these young adolescents [4].…”
Section: Implications and Contributionmentioning
confidence: 99%
“…Major obstacles to reaching elimination of perinatal HIV in the United States have been identified in several recent reports and include late diagnosis of HIV among pregnant women and suboptimal ART for their treatment and prevention of pediatric infections. Geographic and racial disparities of perinatal HIV outcomes continue to point to the Southern States and African American mother-child pairs as most vulnerable 14,15 . Current lack of a national surveillance system for tracking pregnancy outcomes in women living with HIV also needs to be addressed 16 .…”
Section: Introductionmentioning
confidence: 99%